Digital Peer Feedback and Students’ Critical Thinking: What Correlation and to What Extent? - Berliana Dyah Ayu Aprilianti; Agus Widyantoro (Universitas Pendidikan Mandalika, 2024)
Digital peer feedback is one of the valuable instructional activities that can enhance students' critical thinking abilities. Yet, knowing it is an urge, the discussion about this has not been much quantitatively checked by some scholars.Therefore, the purpose of this research is to investigate the relationship between the qualification of perceived of providing digital peer feedback and students' critical thinking. In amplifying the purpose, this current research utilized a quantitative approach with a correlational design. The result shows an overall rating of 3.55 out of 4, indicates that students show a high perception of providing digital peer feedback. The critical thinking score of the students was indicates in the second result (3.82 out of 5), which shows that it is high level of critical thinking. The last finding examines the relationship between students' critical thinking and their perception of the advantages of providing digital peer feedback. The correlation test's significant (2-tailed) value is found to be 0.000 < 0.05 in the result, indicating that the alternative hypothesis (H1) is accepted. The relationship was classified as weak level since the Pearson correlation result (r-value) was 0.358. It concludes that students applied critical thinking skills when providing digital peer feedback, and they also believed that providing digital peer feedback had various benefits for them. The result, it can be used to gain a greater understanding on how students view digital peer feedback, their critical thinking, and the relationship between qualification of perceived of providing digital peer feedback and students' critical thinking.